2022
DOI: 10.1109/tvcg.2020.2976986
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Specular Reflections and Cast Shadows to Estimate Reflectance and Illumination of Dynamic Indoor Scenes

Abstract: The goal of Mixed Reality (MR) is to achieve a seamless and realistic blending between real and virtual worlds. This requires the estimation of reflectance properties and lighting characteristics of the real scene. One of the main challenges within this task consists in recovering such properties using a single RGB-D camera. In this paper, we introduce a novel framework to recover both the position and color of multiple light sources as well as the specular reflectance of real scene surfaces. This is achieved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The Max-ill method directly selects the area with the maximum illumination as the specular reflection point. The method of Jiddi et al (2022) calculates the vector of each highlight region to recover the light source direction. The method of Yi et al (2014) calculates the illuminant directions of the luminance component's three local regions, which meet the requirements of lower complexity and larger average gray value, and synthesize them as the final illuminant direction.…”
Section: Estimation Of Reflected Angle 431 Static Scenariomentioning
confidence: 99%
“…The Max-ill method directly selects the area with the maximum illumination as the specular reflection point. The method of Jiddi et al (2022) calculates the vector of each highlight region to recover the light source direction. The method of Yi et al (2014) calculates the illuminant directions of the luminance component's three local regions, which meet the requirements of lower complexity and larger average gray value, and synthesize them as the final illuminant direction.…”
Section: Estimation Of Reflected Angle 431 Static Scenariomentioning
confidence: 99%
“…Regarding the automatic assessment of illumination artifacts on images, a recent literature review [16] highlighted the crucial impact of shadows on the performance of computer vision applications, which may decrease its performance due to loss or distortion of objects in the acquired image. Additionally, in [17,18], the importance of detecting reflections on image-based solutions is emphasized, since, despite the valuable information that specular reflections may add, their presence is usually a drawback for image segmentation tasks.…”
Section: Related Workmentioning
confidence: 99%
“…An ML pipeline was developed to ensure that the acquired images did not present any illumination artifacts such as shadows or reflections, a key factor to ensure the quality and adequacy of the acquired trap images [16][17][18]. The main goal of this module is to avoid the use of trap images without suitable and homogeneous illumination, which might compromise not only posterior automated steps like trap segmentation or perspective correction, but also key tasks like the correct identification of insects for pest monitoring purposes.…”
Section: Shadows and Reflections Assessment Pipelinementioning
confidence: 99%
“…Recently, Jiddi et al [18] demonstrated illumination estimation using both specular paths and shadow information. Specular paths are a useful cue for estimating incident illumination [16,31] potentially "in the wild," but suitable surfaces must be present in the scene.…”
Section: Incident Illumination Estimationmentioning
confidence: 99%